SUSTAINABLE LANDSCAPE DESIGN CONCEPTS FOR GREEN OPEN SPACE MANAGEMENT - Silia Yuslim; Hendrik Sulistio (Universitas Mercu Buana, 2021)
To achieve the target of 30% of the total area's green space area, causing Jakarta and other big cities to make efforts to accelerate the provision of green space. Efforts to provide and manage it did not go as expected. The problem lies in the planning, implementation, utilization, and control relating to institutions, financing, and community participation. That causes the management of Green Open Space (GOS) is not running effectively and efficiently. The main problem is the unavailability of clear guidelines on implementing green space management and ineffective phasing related to the determination of terms of reference with budget constraints. Based on previous research, the concept of sustainable landscape design in harmony with sustainable development is the right way to solve this problem. This study aims to discuss how the concept of sustainable landscape design can be bundled by governance involved in managing green space using action research based on soft systems methodology. It will provide a conceptual model of packaging efforts so that it becomes a reference in various actions to provide and manage green space to achieve effective and efficient GOS management.